Theories of Nation Building: An Analysis for Academicians and Nation Builders to Employ Nepali Army - Bhat, Anand Sing (Unity Journal, 2021)
Some of the theories of nation building have been dedicated to the study of link between nation and nationalism; others are attributed to explore nation building, state building, social integration, national integration and even conflict transformation during various historical periods. However, nation building is a normative concept used by academicians and nation builders alike to study the role of armed forces in nation building in recent times. Although research has conducted on ethnicity and nation building in Nepal, a little is known about application of theoretical perspective to explore the role of Nepali Army in nation building. Apparently, this article argues that the level of theoretical awareness of academicians and nation builders needs improvement and multiple theories of nation building are relevant to explore the role of Nepali Army in nation building during various enclaves of Nepali nation. Important issues like what are the relevant theories in Nepali context to analyse nation building? Their implication during the historical times to study the link of Nepali Army with nation building needs to be studied. Hence, this paper comparatively examines a nation building theories and their relevant implications during various enclaves of Nepali nation particularly applauding the role on Nepali Army. Conceptual framework based on Saunder's Research Onion Peeled (2007) method was used with qualitative design in a way of inductive approach to conduct the research work to investigate the research questions. Comparative document study, library research, quick survey with policy makers, government employees, professors, university students APF Officers and Army Officers based on purposive sampling method have been used. Study found that Nepali nation passes through its own way of building the nation in various enclaves, none of the theories are complete to study the employment of Nepali Army to produce visible and encouraging results. The level of theoretical awareness of academicians and nation builders needs further improvement. For this, multiple theories particularly related to social transformation, infrastructural development in support of centre to periphery relation; social integration and nationalism are appropriate.